Understanding the relationship between religion and entrepreneurship - Tamzini, Khaled; Ben Salem, Anis (Advances in religious and cultural studies (ARCS) book series, 2019)
""This book explores the methods and applications of religious theology on entrepreneurial decision making"--Provided by publisher"--